Factor Analysis of Physiotherapists on the Implementation of Telephysiotherapy in Indonesia - Lubis, Zidni Imanurrohmah; Tanazza, Syi'ar Aprilla; Sari, Ni Putu Desy Purnama; Rahim, Anita Faradilla; Multazam, Ali (Poltekkes Kemenkes Palu, 2024)
Telephysiotherapy is a long-distance physiotherapy service using technology, including voice or video calls. In Indonesia, telephysiotherapy is not popular compared to abroad, so researchers want to analyze the factors of physiotherapists on implementation of telephysiotherapy in Indonesia. This research was a correlational analytic descriptive study with a cross-sectional approach. The independent variables are the attitude, readiness, knowledge, and motivation of physiotherapists in Indonesia in addition, the dependent variable is the implementation of telephysiotherapy with 117 physiotherapists in Indonesia as subjects. Questionnaire used and tested for validity and reliability. By Chi-Square test, the result found that attitude variable obtained a p-value of 0.034 (p <0.05) and OR value of 2.561, which means that a positive attitude increases the implementation of telephysiotherapy by 2 times, while on the readiness variable the p-value 0.008 (p <0.05) with OR 3.237 which means high readiness increases 3 times the implementation of telephysiotherapy and on the variables of knowledge and motivation shows a p-value of 0.042 (p <0.05) with an OR value of 2.415 which means high knowledge and motivation increase the implementation of telephysiotherapy 2 times greater than low knowledge and motivation. This study found that the majority of physiotherapists in Indonesia have a positive attitude and readiness, knowledge, and high motivation towards the implementation of telephysiotherapy in Indonesia, but more physiotherapists in Indonesia have not implemented telephysiotherapy. On the other hand, there is a relationship between the attitude, readiness, knowledge, and motivation of physiotherapists towards the implementation of telephysiotherapy in Indonesia.